Intracellular ESAT‐6: A new biomarker for Mycobacterium tuberculosis infection. Issue 3 (6th February 2015) - Poulakis, Nikolaos; Gritzapis, Angelos D.; Ploussi, Maria; Leventopoulos, Michail; Papageorgiou, Chrysovalantis V.; Anastasopoulos, Andreas; Constantoulakis, Pantelis; Karabela, Simona; Vogiatzakis, Evangelos; Tsilivakos, Vassilis
Abstract : Background: Early secreted antigenic target 6 (ESAT‐6) is a virulent factor of Mycobacterium tuberculosis (MTB). The identification of intracellular (i/c) ESAT‐6 in host cells would be a direct marker of MTB infection. We developed a method to detect i/cESAT‐6 by flow cytometry. The aim of this study is to investigate the expression of i/cESAT‐6 in the host cells of individuals with MTB infection. Methods: The expression of i/cESAT‐6 was examined in the blood of 58 active TB patients, in 10 naïve to TB infection controls, in 17 patients who completed anti‐TB treatment, and in 56 close contacts with an index TB case. Additionally, it was examined in the sputum of 12 active TB patients. Results: The i/cESAT‐6 was positively detected in the blood of 52 out of 58 (90%) active TB patients. All naïve to TB infection controls were negative. Three out of 17 (18%) patients at the end of anti‐TB treatment were positive. Twenty‐six out of 56 (46%) close contacts tested positive. The i/cESAT‐6 was detected in all culture positive TB sputum specimens. Conclusions: The i/cESAT‐6 is a promising biomarker of MTB infection that could be used in the evaluation of active TB patients and in the diagnosis of latent TB infection. Further studies are needed to validate its potential diagnostic role. © 2014 International Clinical Cytometry Society